Fixed income securities concepts and applications - Parameswaran, Sunil K. (De Gruyter, 2020)
Fixed Income Securities covers the entire gamut of fixed income products, from plain vanilla bonds to interest rate derivatives and mortgage-backed securities. With helpful numerical illustrations and explanations on the use of specific functions in Excel, this book presents essential constructs and concepts, with a simultaneous focus on practical applications and issues of interest to market professionals. Sunil Kumar Parameswaran delves into the time value of money, bonds, yield measures, money markets, interest rate futures, and interest rate swaps to provide an in-depth look at issues pertaining to fixed income securities. This book is an essential resource for professionals in the fields of brokerage, insurance, mutual funds, pension funds, hedge funds, commercial and investment banks, as well as students of finance.